Problems of ensuring the constitutional rights and legitimate interests of prisoners in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2022)
Wide attention to topical issues of the problems of ensuring observance of constitutional rights and freedoms of the individual, as well as the legitimate interests of those sentenced to deprivation of liberty in the Republic of Kazakhstan and their implementation are becoming important in modern conditions. It is known that all committed criminal offenses encroach on the personal rights and freedoms of a person and a citizen. Ensuring the constitutional rights and legitimate interests of those sentenced to deprivation of liberty, guarantees that the state and citizens will fulfill their duties in providing the opportunity to enjoy the rights enshrined in law. This is important, first of all, because a person himself determines the range of information that is confidential or can be disclosed from his personal life, as well as what information he has the right to receive.The article under consideration highlights the issues of ensuring the constitutional rights and legitimate interests of convicts sentenced to deprivation of liberty, reflects the main directions for improving the rights and legitimate interests of convicts in the Republic of Kazakhstan in the execution of sentences. The authors emphasize that convicts, being an integral part of civil society, must be protected by the state with their rights and freedoms, even in isolation. Lack or incomplete provision of this function leads to the discrediting of not only the penitentiary system, but also the entire law enforcement system of the state.Key words: rights, legitimate interests, convict, execution of punishment, institution for the execution of punishment, civil society.